PERUMUSAN STRATEGI RADIO KALTARA 105.8 FM ONLINE DI PROVINSI KALIMANTAN UTARA - Alfaridzi, Rikhard (Jurnal Kewirausahaan dan Inovasi, 2022)
This research is motivated by the author's observations of the development of modern communication media today which has allowed people all over the world to be able to communicate with each other. Radio has undergone quite a long development before becoming a mass communication medium as it is today. The purpose of this study is how the reporting strategy of Radio Kaltara in disseminating information, especially in reporting and what are the strengths and challenges in reporting Radio Kaltara. This research uses descriptive qualitative research which is explorative. This research is located at Radio Kaltara FM, Radio Kaltara FM is sheltered by PT. Media Radio Kaltara which has the tagline Real News & Music Station and is on the 92.4 MHz frequency. The data collected for this study were taken from two sources of data, namely primary and secondary. The results of the analysis obtained from the EFE and IFE matrices are a matrix called the internal-external matrix (IE). These outcomes are selected based on the IFE and EFE scores. SWOT analysis consists of strengths, weaknesses, opportunities, and threats as instruments for forming strategies.